Ghee’s health benefits on cardiovascular health and lipid profile: Insights from a systematic review and meta-analysis - Aulesa, Carlos; Fernandez, Elisa (Progress in Nutrition, 2025)
Background: This study aims to evaluate the clinical evidence on the efficacy and safety of consuming Ghee (clarified butter) for human health. Ghee has been an important part of Indian cuisine for centuries and plays a vital role in Ayurvedic medicine. It is a healthy dietary fat recommended for daily use, but recent studies suggest it might raise the risk of coronary heart disease (CHD). Over the years, studies on this subject have produced inconsistent and conflicting results.Methods: Following Prisma 2020 and Moose guidelines, a systematic review analyzed studies on Ghee's health effects from 1994 to 2024. A total of 919 articles were retrieved from various plataforms.From these,33 were futher selected, and finally,18 were included in the meta-analysisResults: A meta-analysis of ghee consumption and CHD  included 10 clinical and epidemiological study design with 19,948 participants, including 4,558 cases-subsjects from the Indian subcontinent. Using a random-effects model, the CHD risk was ORp: 1.15 (95% CI: 0.71–1.59). Another meta-analysis of eight studies on ghee and lipid profiles found that ghee intake had neutral to positive effects on lipid levels.Conclusion: This review and meta-analysis aimed to clarify the conflicting information regarding the health effects of Ghee consumption. Our findings indicate that Ghee consumption is associated with a marginally increased risk of coronary heart disease (CHD). However, Ghee consumption does not appear to have a significant impact on the overall lipid profile in humans. These results underscore the need for further research to explore the mechanisms underlying these associations and to provide more definitive guidance on the health implications of Ghee consumption.